Math hysteria : fun and games with mathematics - Stewart, Ian, 1945- (Oxford University Press, 2004)
Welcome to Ian Stewart's strange and magical world of mathematics! In Math Hysteria, Professor Stewart presents us with a wealth of magical puzzles, each one spun around an amazing tale: Counting the Cattle of the Sun; The Great Drain Robbery; and Preposterous Piratical Predicaments; to name but a few. Along the way, we also meet many curious characters: in short, these stories are engaging, challenging, and lots of fun!